The effect of local government information system training, work environment and motivation on employee performance - Rolanda, M. Fitra Marsha; Hasmawaty, Hasmawaty (Institute of Computer Science (IOCS), 2024)
The important role of employees in achieving performance cannot be ignored, their abilities must be proven so that they are able to carry out their duties properly and produce optimal performance. The purpose of this study was to determine and analyze the effect of LGIS training, work environment and motivation on employee performance. Researchers took all employees of the Regional Financial and Asset Management Agency of Musi Banyuasin Regency as a population of 74 people and all of them were taken as samples. Analysis techniques and hypothesis testing using quantitative methods with SEM PLS. The results showed that the variables of local government information system training and work environment had an effect on employee performance while motivation had no effect on employee performance.